A silicon-based negative electrode material with high specific capacity and long cycle life and a preparation method thereof

By adopting Si-Al-N-C three-dimensional hollow microsphere structure, the silicon-based anode material is solved, and the battery performance with high specific capacity and long cycle life is achieved, which significantly extends the battery life.

CN118598682BActive Publication Date: 2025-03-07武汉聚东芯电科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410637609.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-03-07
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The capacity increase of existing lithium-ion battery negative electrode materials such as graphite has reached its limit, and the volume changes of silicon materials during charging and discharging, resulting in poor cycling performance of active substances, limiting its wide application in the lithium battery industry.

Method used

Si-Al-N-C three-dimensional hollow microsphere structure was adopted to add hexagonal silicon nitride, alumina, boron nitride and silicon carbide powder to the citric acid solution, and then stirred in ultrasonic to the ethanol solution for oil bath evaporation to form a hollow microsphere template. Then immerse it in ceramic slurry to sinter, obtain a dense ceramic skeleton and undergo a second sintering to prepare a silicon-based negative electrode material with excellent electrochemical properties.

Benefits of technology

This silicon-based negative electrode material has a high specific capacity and a long cycle life, which can effectively buffer volume expansion, prevent electrode rupture and capacity attenuation, and the first discharge specific capacity reaches 2889mAh/g. The capacity retention rate after 20 cycles is high, which significantly extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004852280400000061
    Figure BDA0004852280400000061
  • Figure BDA0004852280400000071
    Figure BDA0004852280400000071
Patent Text Reader

Abstract

The present invention provides a silicon-based negative electrode material with high specific capacity and long cycle life and a preparation method thereof, the steps comprising: S1, dissolving citric acid in water, adding hexagonal silicon nitride, aluminum oxide, boron nitride and silicon carbide powder in sequence, ultrasonic stirring, adding polyvinyl alcohol, and continuing stirring to obtain a precursor solution; S2, dripping the precursor solution into an ethanol solution, evaporating in an oil bath, collecting and drying to obtain a hollow microsphere template; S3, immersing the hollow microsphere template in a ceramic slurry, vacuum filtering, sintering, and cooling with the furnace to obtain a dense ceramic skeleton; S4, grinding the dense ceramic skeleton, compacting and molding, and sintering again to obtain the target silicon-based negative electrode material. The first discharge specific capacity of the silicon-based negative electrode material assembled battery of the present invention reaches 2889mAh / g, reduces the full charge expansion rate of the battery, prolongs the cycle life of the battery, effectively buffers and inhibits volume expansion, and after 20 cycles of charge and discharge, the battery maintains a high capacity retention rate, and the capacity will not be greatly attenuated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a silicon-based negative electrode material with high specific capacity and long cycle life and a preparation method thereof. Background Art

[0002] Most of the current negative electrode materials for lithium-ion batteries use traditional graphite materials, which have a theoretical capacity of 372mAh / g and cannot meet the needs of the future development of electric vehicles. Therefore, developing high-performance negative electrode materials for lithium-ion batteries with fast charging, high energy density and long service life is the key to the development of electric vehicles, and also the key to achieving green environmental protection and alleviating environmental pollution.

[0003] At present, the negative electrode material of commercial batteries is still mainly graphite. The capacity improvement of graphite has almost reached its limit. The development of higher and better new battery negative electrode materials is the only way to meet market demand. Silicon is currently one of the best choices for battery negative electrodes. The theoretical specific capacity of silicon materials is high, reaching 4200mAh / g, and the reaction activity with electrolytes is low, and the discharge platform is also relatively low. However, the silicon material is accompanied by volume changes (up to 300%) during the charging and discharging process, which causes the active material to be crushed, causing the active material to fall off from the current collector, and ultimately causing a sharp decrease in capacity. In addition, due to the severe volume expansion and contraction of the silicon negative electrode during the lithium extraction process, the battery's cycle performance is poor, limiting its wide application in the lithium battery industry.

[0004] Therefore, the present invention aims to provide a silicon-based negative electrode material, which has high cycle performance and high specific capacity, and can be prepared by a simple process and is suitable for mass production. Summary of the invention

[0005] In view of this, the present invention proposes a silicon-based negative electrode material with high specific capacity and long cycle life and a preparation method thereof. When the silicon-based negative electrode material of the present invention is applied to lithium-ion batteries, it exhibits high cycle performance and high specific capacity, has excellent electrochemical properties, and after multiple cycles, the capacity will not be significantly attenuated.

[0006] The technical solution of the present invention is achieved in this way:

[0007] A method for preparing a silicon-based negative electrode material with high specific capacity and long cycle life, the specific steps comprising:

[0008] S1. Dissolve citric acid in water, add hexagonal silicon nitride, aluminum oxide, boron nitride and silicon carbide powders in sequence, stir ultrasonically, add polyvinyl alcohol, continue stirring, and obtain a precursor solution;

[0009] S2, dropping the precursor solution into an ethanol solution, evaporating in an oil bath, collecting and drying to obtain a hollow microsphere template;

[0010] S3, immersing the hollow microsphere template into the ceramic slurry, vacuum filtering, sintering, and cooling with the furnace to obtain a dense ceramic skeleton;

[0011] S4. Grind the dense ceramic skeleton, compact it into shape, and sinter it again to obtain the target silicon-based negative electrode material.

[0012] Furthermore, in step S1, in parts by weight, the citric acid is 1-3 parts, the water is 200-300 parts, the hexagonal silicon nitride is 40-60 parts, the aluminum oxide is 10-20 parts, the boron nitride is 5-15 parts, the silicon carbide is 5-15 parts, and the polyvinyl alcohol is 2-5 parts.

[0013] Furthermore, in step S1, the speed of the ultrasonic stirring is 600-800 rpm, and the time is 1-3 h; the time of continued stirring is 30-60 min.

[0014] Furthermore, in step S2, the volume ratio of the ethanol solution to the precursor solution is 10-20:1, and the concentration is 60%-80% v / v; the temperature of the oil bath is 100-140° C., and the time is 2-4 hours.

[0015] Furthermore, in step S3, the solid content of Si-Al-N in the ceramic slurry is 30-50wt%; the sintering temperature is 1400-1600°C, and the sintering time is 2-4h.

[0016] Furthermore, in step S4, the grinding time is 40-60 min; the sintering temperature is 1200-1400° C., and the sintering time is 1-2 h.

[0017] A silicon-based negative electrode material with high specific capacity and long cycle life is prepared by the preparation method described above.

[0018] Furthermore, the silicon-based negative electrode material is Si-Al-NC three-dimensional hollow microspheres.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The silicon-based negative electrode material prepared by the present invention is a Si-Al-NC three-dimensional hollow microsphere structure, which can effectively buffer volume expansion and improve cycle stability. Silicon-based negative electrode materials have excellent conductivity, mechanical strength and chemical stability. The three-dimensional hollow microsphere structure provides high porosity and specific surface area, provides more active sites and faster diffusion channels for lithium ions, and promotes the penetration of electrolytes. The silicon-based negative electrode material of the present invention has strong structural stability to prevent collapse, can effectively buffer volume expansion, and prevent electrode rupture and capacity decay. The embodiment confirms that the first discharge specific capacity reaches up to 2889mAh / g, which significantly reduces the full-charge expansion rate of the battery, prolongs the cycle life of the battery, effectively buffers and inhibits volume expansion. After 20 cycles of charge and discharge, the battery maintains a high capacity retention rate and the capacity will not decay significantly.

[0021] 2. Si-Al-NC three-dimensional hollow microspheres have a large internal cavity and a thin shell layer. The internal cavity can accommodate the insertion / deinsertion of lithium ions, thereby reducing the volume expansion of silicon-based negative electrode materials and improving the cycle life of the battery. Si-Al-NC three-dimensional hollow microspheres provide a large amount of electrolyte-electrode contact area, shorten the lithium ion diffusion path, increase the charge and discharge rate, and have a high specific capacity. The silicon-based negative electrode material of the present invention can be prepared by a simple process and is suitable for mass production. DETAILED DESCRIPTION

[0022] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0023] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0024] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0025] Example 1

[0026] A method for preparing a silicon-based negative electrode material with high specific capacity and long cycle life, the specific steps comprising:

[0027] S1. Dissolve 2 g of citric acid in 250 mL of water, add 50 g of hexagonal silicon nitride, 15 g of aluminum oxide, 10 g of boron nitride and 10 g of silicon carbide powder in sequence, stir ultrasonically at a speed of 700 rpm for 2 h, add 3 g of polyvinyl alcohol, and continue stirring for 45 min to obtain a precursor solution;

[0028] S2, dropping the precursor solution into 70% v / v ethanol solution at a volume ratio of 15:1, evaporating in an oil bath at 120°C for 3 h, collecting and drying to obtain a hollow microsphere template;

[0029] S3, immersing the hollow microsphere template in a ceramic slurry with a Si-Al-N solid content of 40wt%, vacuum filtering, raising the temperature to 1500°C for sintering for 3h, and cooling with the furnace to obtain a dense ceramic skeleton;

[0030] S4. Grind the dense ceramic skeleton for 50 minutes, compact it into shape, raise the temperature to 1300°C and perform a second sintering for 1.5 hours to obtain the target silicon-based negative electrode material.

[0031] Example 2

[0032] A method for preparing a silicon-based negative electrode material with high specific capacity and long cycle life, the specific steps comprising:

[0033] S1. Dissolve 1 g of citric acid in 200 mL of water, add 40 g of hexagonal silicon nitride, 10 g of aluminum oxide, 5 g of boron nitride and 5 g of silicon carbide powder in sequence, stir ultrasonically at a speed of 600 rpm for 1 h, add 2 g of polyvinyl alcohol, and continue stirring for 30 min to obtain a precursor solution;

[0034] S2, dropping the precursor solution into a 60% v / v ethanol solution at a volume ratio of 10:1, evaporating in an oil bath at 100°C for 2h, collecting and drying to obtain a hollow microsphere template;

[0035] S3, immersing the hollow microsphere template in a ceramic slurry with a solid content of Si-Al-N of 30 wt%, vacuum filtering, raising the temperature to 1400°C for sintering for 2 h, and cooling with the furnace to obtain a dense ceramic skeleton;

[0036] S4. Grind the dense ceramic skeleton for 40 minutes, compact it into shape, raise the temperature to 1200°C and perform a second sintering for 1 hour to obtain the target silicon-based negative electrode material.

[0037] Example 3

[0038] A method for preparing a silicon-based negative electrode material with high specific capacity and long cycle life, the specific steps comprising:

[0039] S1. Dissolve 3 g of citric acid in 300 mL of water, add 60 g of hexagonal silicon nitride, 20 g of aluminum oxide, 15 g of boron nitride and 15 g of silicon carbide powder in sequence, stir ultrasonically at a speed of 800 rpm for 3 h, add 5 g of polyvinyl alcohol, and continue stirring for 60 min to obtain a precursor solution;

[0040] S2, dropping the precursor solution into 80% v / v ethanol solution at a volume ratio of 20:1, evaporating in an oil bath at 140°C for 4 h, collecting and drying to obtain a hollow microsphere template;

[0041] S3, immersing the hollow microsphere template in a ceramic slurry with a Si-Al-N solid content of 50wt%, vacuum filtering, raising the temperature to 1600°C for sintering for 4h, and cooling with the furnace to obtain a dense ceramic skeleton;

[0042] S4. Grind the dense ceramic skeleton for 60 minutes, compact it into shape, raise the temperature to 1400°C and perform a second sintering for 2 hours to obtain the target silicon-based negative electrode material.

[0043] Comparative Example 1

[0044] Compared with Example 1, this comparative example uses silicon nanoparticles instead of hexagonal silicon nitride and silicon carbide, and uses aluminum nitrate instead of aluminum oxide. Other details are consistent with Example 1.

[0045] A method for preparing a silicon-based negative electrode material with high specific capacity and long cycle life, the specific steps comprising:

[0046] S1. Dissolve 2 g of citric acid in 250 mL of water, add 60 g of silicon nanoparticles, 15 g of aluminum nitrate and 10 g of boron nitride powder in sequence, stir ultrasonically at 700 rpm for 2 h, add 3 g of polyvinyl alcohol, and continue stirring for 45 min to obtain a precursor solution;

[0047] S2, dropping the precursor solution into 70% v / v ethanol solution at a volume ratio of 15:1, evaporating in an oil bath at 120°C for 3 h, collecting and drying to obtain a hollow microsphere template;

[0048] S3, immersing the hollow microsphere template in a ceramic slurry with a Si-Al-N solid content of 40wt%, vacuum filtering, raising the temperature to 1500°C for sintering for 3h, and cooling with the furnace to obtain a dense ceramic skeleton;

[0049] S4. Grind the dense ceramic skeleton for 50 minutes, compact it into shape, raise the temperature to 1300°C and perform a second sintering for 1.5 hours to obtain the target silicon-based negative electrode material.

[0050] Comparative Example 2

[0051] Compared with Example 1, this comparative example lacks hexagonal silicon nitride, and the amount of silicon carbide is increased by 60 parts, and the rest is consistent with Example 1.

[0052] A method for preparing a silicon-based negative electrode material with high specific capacity and long cycle life, the specific steps comprising:

[0053] S1. Dissolve 2 g of citric acid in 250 mL of water, add 15 g of aluminum oxide, 10 g of boron nitride and 60 g of silicon carbide powder in sequence, stir ultrasonically at a speed of 700 rpm for 2 h, add 3 g of polyvinyl alcohol, and continue stirring for 45 min to obtain a precursor solution;

[0054] S2, dropping the precursor solution into 70% v / v ethanol solution at a volume ratio of 15:1, evaporating in an oil bath at 120°C for 3 h, collecting and drying to obtain a hollow microsphere template;

[0055] S3, immersing the hollow microsphere template in a ceramic slurry with a Si-Al-N solid content of 40wt%, vacuum filtering, raising the temperature to 1500°C for sintering for 3h, and cooling with the furnace to obtain a dense ceramic skeleton;

[0056] S4. Grind the dense ceramic skeleton for 50 minutes, compact it into shape, raise the temperature to 1300°C and perform a second sintering for 1.5 hours to obtain the target silicon-based negative electrode material.

[0057] Comparative Example 3

[0058] A method for preparing a silicon-based negative electrode material with high specific capacity and long cycle life, the specific steps comprising: mixing 50g of hexagonal silicon nitride, 15g of aluminum oxide, 10g of boron nitride and 10g of silicon carbide powder, grinding for 50 minutes, compacting and molding, raising the temperature to 1500°C and sintering for 3 hours in a nitrogen atmosphere, and cooling with the furnace to obtain the target silicon-based negative electrode material.

[0059] Performance Testing

[0060] Using copper foil as the current collector, the silicon-based negative electrode material, binder, and conductive agent prepared in the above Examples 1-3 and Comparative Examples 1-3 were mixed in a mass ratio of 8:1:1, stirred, and the mixture was prepared into a slurry using NMP (N-methylpyrrolidone). The slurry was coated on the current collector with a surface density of 8 mg / cm 2 After rolling, the negative electrode sheet is obtained, the negative electrode sheet, the separator and the positive electrode sheet (with lithium nickel cobalt manganese oxide as the positive electrode material) are stacked in sequence, and the bare battery cell is wound. The tabs are welded, and the bare battery cell is placed in a soft-pack aluminum-plastic film, the top and side are sealed, and the electrolyte (1 mol / L LiPF6 ethyl carbonate + dimethyl carbonate (volume ratio 1:1)) is injected. After the top is sealed, the secondary battery is obtained by formation, constant volume, exhaust and sealing, and the performance is tested.

[0061] Testing indicators: first discharge specific capacity; 20th cycle capacity retention rate; full charge expansion rate.

[0062] The test method for the battery cycle capacity retention rate is as follows: charge with a current of 0.5 times the battery capacity and discharge with a current of 1 times the battery capacity for 20 cycles, and calculate the capacity retention rate at the 20th cycle. The capacity retention rate is calculated by the following formula:

[0063] 20th cycle capacity retention rate (%) = 20th cycle discharge capacity / first cycle discharge capacity × 100%

[0064] Among them, the test method of the battery full charge expansion rate is: fully charge the battery with a current of 0.5 times the battery capacity, disassemble it, measure the thickness of the negative electrode sheet after full charge, compare it with the thickness after rolling, and calculate the full charge expansion rate. The full charge expansion rate is calculated by the following formula:

[0065] Full charge expansion rate (%) = (thickness of negative electrode sheet after full charge - thickness of negative electrode sheet after rolling) / thickness of negative electrode sheet after rolling × 100%

[0066] The test results are shown in Table 1.

[0067] Table 1

[0068]

[0069]

[0070] As can be seen from Table 1, the first discharge specific capacity of the negative electrode materials prepared in Examples 1-3 of the present invention reached up to 2889 mAh / g, which significantly reduced the full charge expansion rate of the battery, extended the cycle life of the battery, effectively buffered and inhibited volume expansion, and after 20 cycles of charge and discharge, the battery maintained a high capacity retention rate. The difference between Comparative Example 1 and Example 1 is that hexagonal silicon nitride and silicon carbide are replaced by silicon nanoparticles, and aluminum nitrate is used instead of aluminum oxide. The difference between Comparative Example 2 and Example 1 is that hexagonal silicon nitride is missing. Comparative Example 3 uses a conventional preparation method to prepare a silicon-based negative electrode material, and the first discharge specific capacity, full charge expansion rate and 20-cycle capacity retention rate of the assembled battery are all reduced to varying degrees.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a silicon-based negative electrode material with high specific capacity and long cycle life, characterized in that: The specific steps include: S1. Dissolve citric acid in water, add hexagonal silicon nitride, aluminum oxide, boron nitride and silicon carbide powders in sequence, stir ultrasonically, add polyvinyl alcohol, continue stirring, and obtain a precursor solution; According to the mass percentage, citric acid is 1-3 parts, water is 200-300 parts, hexagonal silicon nitride is 40-60 parts, aluminum oxide is 10-20 parts, boron nitride is 5-15 parts, silicon carbide is 5-15 parts, and polyvinyl alcohol is 2-5 parts; S2, dropping the precursor solution into an ethanol solution, evaporating in an oil bath, collecting and drying to obtain a hollow microsphere template; The volume ratio of the ethanol solution to the precursor solution is 10-20:1; the concentration of the ethanol solution is 60%-80% v / v; the temperature of the oil bath is 100-140° C., and the time is 2-4 hours; S3, immersing the hollow microsphere template into the ceramic slurry, vacuum filtering, sintering, and cooling with the furnace to obtain a dense ceramic skeleton; The solid content of Si-Al-N in the ceramic slurry is 30-50wt%; the sintering temperature is 1400-1600°C and the sintering time is 2-4h; S4, grinding the dense ceramic skeleton, compacting it into a shape, and sintering it again to obtain the target silicon-based negative electrode material; The grinding time is 40-60 minutes; the re-sintering temperature is 1200-1400° C. and the time is 1-2 hours.

2. The method for preparing a silicon-based negative electrode material with high specific capacity and long cycle life according to claim 1, characterized in that: In step S1, the speed of the ultrasonic stirring is 600-800 rpm, and the time is 1-3 hours; the time of continued stirring is 30-60 minutes.

3. A silicon-based negative electrode material with high specific capacity and long cycle life, characterized in that: Prepared by the preparation method according to claim 1 or 2.